Does MCH play a role on establishment or maintenance of social hierarchy in Nile tilapia? - Ramanzini, Guilherme Correa; Volpato, Gilson Luiz [UNESP]; Visconti, Maria Aparecida (Elsevier B.V., 2018)
Body coloration has a fundamental role in animal communication by signaling sex, age, reproductive behavior, aggression, etc. Nile-tilapia exhibits dominance hierarchy and the dominants are paler than subordinates. During social interactions in these animals, these color changes occur rapidly, and normally the subordinates become dark. In teleosteans, from the great number of hormones and neurotransmitters involved in color changes, melanocyte hormone stimulates (alpha-MSH) and melanin concentrates hormone (MCH) are the most remarkable. The aim of this project was to investigate the role of MCH in the establishment of hierarchical dominance of the Nile-tilapia. We analyzed the effect of background coloration in the dominance hierarchy. It was then compared to the melanophore sensibility of dominants and subordinates' fishes to MCH; finally, it was checked if the social rank affects the number of these pigment cells in dominants and subordinated fishes. Fishes which have a social hierarchy established and adjusted individually to the background exhibits paler body coloration when a visual contact was possible, independently of previous social rank and background color. Probably, even recognizing each other, fishes could be defending their new territory. Melanophores of the subordinate fishes were more sensible to MCH than dominants. It suggests that dominants fishes, which are paler than subordinates, could be under a chronic effect of MCH, which could be due a desensitization of melanophores to this hormone. The opposite effect seems to be occurring on subordinate fishes. It was not observed a significant change in the number of melanophores when the fishes were exposed to a prolonged period of agonistic interaction. It is possible that the exposure time for this interaction might not have been sufficient to have any change in the number of these cells of dominants and subordinate fishes.
Keywords: MCH; Melanotropins; Melanophores; Agonistic interaction; Social hierarchy; Nile tilapia; Oreochromis niloticus